20th Biennial BDS Conference 2018 – Tour 1: Caerphilly Castle. Issue 1 (29th March 2019) - Griffin, Orla
Abstract : This paper is an account of the 20th Biennial British Dam Society Conference 2018 – Site Tour 1: Caerphilly Castle. Caerphilly Castle is the second largest castle in the United Kingdom and is surrounded by an inner and outer moat, which is impounded by earth embankments. This paper describes the general background of the visits, including some of the challenges that have arisen with the moats through the years and the work done to resolve them.